Analysis of insecure configurations in Chrome Web Store extensions: Impact on user security and privacy - Silva, José R. S.; Silva, Luiz H. B. A.; Silva, Vitória B. A.; Damasceno, Maria Gabriela Lima; Souza, Caio B. de; Balieiro, Andson (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2025: Anais do XXV Simpósio Brasileiro de Cibersegurança, 2025)
Browser extensions, popular for enhancing functionality, pose risks to user privacy and security. This study analyzes insecure configurations in Chrome Web Store extensions, assessing their functional justification. Auditing 287 extensions revealed that many employ excessive permissions or unnecessary access to sensitive data without clear justification. Findings show that risky practices persist even in widely used tools, highlighting flaws in app stores’ verification processes. The research provides empirical evidence of these issues and advocates for stricter policies for developers, platforms, and regulators to balance functionality and security in the ecosystem.